Dynamic optical coherence tomography shows characteristic alterations of blood vessels in malignant melanoma. (5th January 2021) - Welzel, J.; Schuh, S.; De Carvalho, N.; Themstrup, L.; Ulrich, M.; Jemec, G.B.E.; Holmes, J.; Pellacani, G.
Abstract: Background: Dynamic optical coherence tomography (D‐OCT) allows in vivo visualization of blood vessels in the skin and in malignant tumours. Vessel patterns in malignant melanoma may be associated with tumour stage. Objective: The aim of this study was to describe blood vessel patterns in melanomas and to correlate them with stage. Methods: One hundred fifty‐nine malignant melanomas were assessed in a multicentre study. Every tumour was imaged using D‐OCT prior to surgery and histologic evaluation. The tumour data such as thickness and ulceration as well as the staging at primary diagnosis and a follow‐up of at least 40 months resulted in a stage classification. The vessel patterns were assessed according to predefined categories, compared with healthy adjacent skin, and correlated to stage. Results: Melanomas contained more blood vessels in different patterns compared with healthy adjacent skin. In particular, irregular vascular shapes such as blobs, coils, curves and serpiginous vessels were more common in melanomas. In addition, these patterns were significantly more often found in high‐risk and metastatic melanomas than in low‐risk lesions. Conclusion: In melanomas, the density of the blood vessels is increased, and irregular vascular patterns are more frequent. At higher stages, especially in metastatic melanomas, these atypical vessels are significantly more common.